HOW DOES ESG SCORE AND BOARD STRUCTURE AFFECT ON FINANCIAL PERFORMANCE? EVIDENCE FROM ESG SECTOR LEADERS IDX KEHATI - Rizki Syaputra, Arifa
The rise of sustainable investing, an investing strategy considering ESG (environmental, social, governance) factor of the company has spread worldwide, including in Indonesia. Recent phenomena of minimum percentage of woman on board in state-owned enterprise policy by Indonesia Ministry of State-Owned Enterprise and the new two ESG themed index which consists of state-owned enterprise has intrigued to assess the relationship between board structure towards financial performance of the companies. One of the index is “ESG Sector Leaders IDX KEHATI“ which comprises of stocks with an ESG performance assessment above their industrial average value. This study harness “Pooled OLS Robust Regression” to assess how ESG score and board structure affect financial performance of “ESG Sector Leaders IDX KEHATI”. Using ROA and ROE as the dependent variable and ESG and board structure variables, and firm size as independent variable, asset to equity ratio, and firm age as control variables. It is found that ESG has negative non-significant relationship towards both ROA and ROE. Board independence and board gender diversity has positive significant effect towards both ROA and ROE.